Work Engagement as A Mediator of Service Leadership to Lecturers’ Performance - Purwaningtyas, Endah Kurniawati (Proceedings Conference Psychology and Flourishing Humanity; Vol 1 No 1 (2024): Proceedings Conference on Psychology and Flourishing Humanity, 2025)
Performance is one of the important things in achieving organizational goals. The performance of lecturers in universities is different from performance in business-oriented organizations. The performance of lecturers in higher education aims to achieve organizational goals through the elements regulated in Law No. 14 of 2005. These elements include educational and teaching activi- ties, research, community service, and other support. This research aims to analyze the influence of perceptions of ser- vice leadership on lecturer performance through work engagement as a mediating variable. This research used a quantitative approach and survey method, conducted on 148 civil servants (ASN) lectur- ers who had lecturer certification status (lecturer certification) from two A-accredited state Islamic religious universities in East Java. The data collection tools are four questionnaires and one re- cap of lecturer performance scores. The results of this research show that the theoretical model of lecturer performance consisting of perceptions of service leadership and work engagement contrib- utes to lecturer performance and is supported by empirical data. This research found that to improve lecturer performance, it is nec- essary to pay attention to the work engagement factor which is the strongest and most significant antecedent as a real mediator of ser- vice leadership perceptions of lecturer performance.